Efektivitas Model Pembelajaran Discovery LearningTerhadap Hasil Belajar Matematika Peminatan (Studi Kasus Peserta Didik Kelas XII IPA MAN Alor) - Lang Ere, Rahmatia (Jurnal Pendidikan Madrasah, 2024)
This research aims to determine the effectiveness of the Discovery Learning model on Mathematics Specialization learning outcomes. The population of this research was 171 students of Madrasah Aliyah Negeri Alor Class XII Science for the 2023/2024 academic year. The research sample was Class XII IPA 2 as the experimental class and Class XII IPA 3 as the control class. This research design uses a pretest-posttest control group design. Data was collected through a written test with questions in the form of descriptions. Data were analyzed using the N-Gain Score Test which was preceded by the Normality Test and Difference Test. The research results show that the Discovery Learning model is quite effective in improving the learning outcomes of Class XII IPA MAN Alor students for the 2023/2024 academic year.